2020
DOI: 10.7717/peerj.9936
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of PRR gene family uncovers their roles in circadian rhythmic changes and response to drought stress in Gossypium hirsutum L.

Abstract: Background The circadian clock not only participates in regulating various stages of plant growth, development and metabolism, but confers plant environmental adaptability to stress such as drought. Pseudo-Response Regulators (PRRs) are important component of the central oscillator (the core of circadian clock) and play a significant role in plant photoperiod pathway. However, no systematical study about this gene family has been performed in cotton. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 101 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…The temperature and light cycle were set at 24 °C with a 14 h/10 h (light and dark) photoperiod. After two days of culture, the seedlings were treated with 400 mM PEG6000 [ 64 ] and 150 mM NaCl treatment [ 65 ], respectively. The control groups were set for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature and light cycle were set at 24 °C with a 14 h/10 h (light and dark) photoperiod. After two days of culture, the seedlings were treated with 400 mM PEG6000 [ 64 ] and 150 mM NaCl treatment [ 65 ], respectively. The control groups were set for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of genome-wide gene expression revealed that the core components of the clock are conserved between plant species [ 24 , 25 ]. In Arabidopsis , the circadian clock is composed of a negative feedback loop comprising three inhibitory steps [ 26 , 27 ].…”
Section: How Does the Circadian Clock Work?mentioning
confidence: 99%
“…The obvious rhythmic expression trend with PEG treatment as well as qRT-PCR verification of PEG-induced expression of several members of the PRR gene family uncovered the involvement of GhPRR in drought-stress response in Gossypium hirsutum [ 25 ]. In Arabidopsis , expression of drought-stress-response genes including DREB1/CBF (DEHYDRATION-RESPONSIVE ELEMENT B1/C-REPEAT-BINDING FACTOR) was conferred in prr9 prr7 prr5 mutants [ 98 ].…”
Section: Circadian Clock Enhances Fitness By Improving Plant Drought-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive use of chemical fertilizers, especially N fertilizers, increases the cost of crop production and greenhouse gas emissions, as well as soil and groundwater pollution 9 , 10 . Therefore, optimization of crop production under nitrogen restriction conditions is a major challenge in agriculture 11 .…”
Section: Introductionmentioning
confidence: 99%